THE RELATIONSHIP BETWEEN THE DIMENSION OF ANTENATAL CARE SERVICE QUALITY WITH THE PATIENT'S SATISFACTION AND THE INTEREST IN REVISITATION AT THE GONDANGLEGI PRIMARY HEALTH CENTER, MALANG REGENCY - Budiarti, Maulida; Ratnaningrum, Safrina Dewi; Indriani, Anin (Journal of Community Health and Preventive Medicine, 2024)
Antenatal care (ANC) is planned to prepare for a safe and comfortable delivery. Assessment of the quality of care received by patients is used as a guide to determine the best and weakest dimensions of service quality. Service quality aspects are evaluated based on five quality service dimensions, including tangible, reliability, responsiveness, assurance, and empathy. The purpose of this study is to analyze the relationship between the five dimensions of ANC service quality and patient satisfaction and revisit interest. The method in this study uses a quantitative research design with a cross-sectional approach, with a sample size of 86 pregnant mothers. Sampling was done using accidental sampling. Data were analyzed using chi-square. The results show that the tangible dimension has the strongest influence on satisfaction (OR 104.50) and revisit interest (OR 41.08) of patients in the KIA clinic at Puskesmas Gondanglegi. The conclusion from this study is the existence of a relationship between the dimensions of ANC service quality, including tangible, reliability, responsiveness, assurance, and empathy, with patient satisfaction and revisit interest in the maternal-children clinic at Gondanglegi primary health center.